Radix Astragali and Its Representative Extracts for Diabetic Nephropathy: Efficacy and Molecular Mechanism - Hui-zhong Xue; Yu Chen; Shi-dong Wang; Yi-meng Yang; Lu-qi Cai; Jin-xi Zhao; Wei-jun Huang; Yong-hua Xiao (Journal of Diabetes Research)
Diabetic nephropathy (DN) is a common microvascular complication of diabetes mellitus (DM). Radix Astragali (RA), a frequently used Chinese herbal medicine in the Leguminosae family, Astragalus genus, with its extracts, has been proven to be effective in DN treatment both in clinical practice and experimental studies. RA and its extracts can reduce proteinuria and improve renal function. They can improve histopathology changes including thickening of the glomerular basement membrane, mesangial cell proliferation, and injury of endothelial cells, podocytes, and renal tubule cells. The mechanisms mainly benefited from antioxidative stress which involves Nrf2/ARE signaling and the PPARγ-Klotho-FoxO1 axis; antiendoplasmic reticulum stress which involves PERK-ATF4-CHOP, PERK/eIF2α, and IRE1/XBP1 pathways; regulating autophagy which involves SIRT1/NF-κB signaling and AMPK signaling; anti-inflammation which involves IL33/ST2 and NF-κB signaling; and antifibrosis which involves TGF-β1/Smads, MAPK (ERK), p38/MAPK, JNK/MAPK, Wnt/β-catenin, and PI3K/AKT/mTOR signaling pathways. This review focuses on the clinical efficacy and the pharmacological mechanism of RA and its representative extracts on DN, and we further document the traditional uses of RA and probe into the TCM theoretical basis for its application in DN.